The Movement Patterns of Tourist Destination Floating Market, Lembang, West Bandung Regency - Heryanti; Oot Hotimah; Ilham B Mataburu (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2019)
This research aims to know the movement patterns of tourist destinationfloating market, Lembang, West Bandung Regency. The method used inthis research is descriptive method with a survey approach. The studylasted from June to July 2019. The indicators are (1) the number oftourist visits each tourist destination, (2) motivation of tourist visits, (3)length of stay, (4) modes of transportation, (5) accessibility to touristdestinations, (6) traveling experience, (7) number of travelingcompanions, (8) tourist attraction. The results showed tourists fromBanten Province tended to only make Multiple Patterns with the type ofChaining Loop and Stopover. The age of 17-30 years dominates the eraof tourists; these tourists do tours with their families as much as 100%.Tourists travel time from the origin area to tourist area is 4 to 5 hours, sotourists further shorten the time of visiting each destination anddestinations visited by more tourists.